Analisis Jumlah Fi’liyyah Murakkabah Dan Jumlah Fi’liyyah Muzdawijah Dalam Surah Al-Qashash - Dessy Sintari Daoed; Rabiatul Adawiyah Madawat M (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Linguistic studies of the Qur’an continue to develop, especially in grammatical analysis regarding verbal structures. Surah Al-Qashash presents a variety of verb forms that do not merely appear as singular verbs, but also as composite (murakkab) and dual-meaning (mużdawij) verbs that produce deeper semantic interpretation. This study aims to identify, describe, and analyze the forms of fi’il murakkab and fi’il mużdawij found in Surah Al-Qashash using a qualitative descriptive approach based on textual analysis. The primary data consist of ten examples of fi’il murakkab and ten examples of fi’il mużdawij classified according to contemporary morphology theory. The findings demonstrate that the fi’il murakkab in this surah are mainly formed through combinations of verbs with direct objects, attached pronouns, prepositions, and adverbial components, while the fi’il mużdawij are divided into several types such as tadmin, supplication, cause–effect, conditionality, admiration, and reproach. Each verbal form contributes meaningfully to the semantic layer of the verse and enhances the stylistic dimension of the Qur'an. This research affirms that Qur’anic morphological analysis requires understanding not only word formation but also the semantic relations embedded within sentence structures.